REVISI PSAK NO. 31 - Herry Hutabarat (Jurnal Akuntansi Bisnis, 2017)
Recently banking industry has become general financial-service providers not only in its traditonal role as  intermediator role,  but including  as  payments role,  guarantor role, risk management role, investment banking role, saving/investment advisor role, safe keeping role, agency role, policy role among others. Banking industry in Indonesia still has more significant role as sources of finance than the equity markets in economic development. We agree that  acccounting has responsibility and  must respond  to the ever changing information needs of stakeholders. From experience based on research of PT Bank Mandiri Tbk, which was published since 2005 to 2007, we realize that Indonesian Financial Standard Accounting Statement no. 31 for banking industri (PSAK no.31), has no longer accomodated the measurement, disclosure and auditing of Banking Industry services. Similar isusses have happened  when we have compare PSAK no. 31 to International Financial Accounting Standards. Due to such issues, the Revision of PSAK no. 31 is extreemely needed.   Keywords : Revision,  PSAK No.31,  Banking Industr